Implementation of The Preparation of Teaching Modules in Improving Teachers' Professional Competence (Case Study of Teachers of SMPN 1 Integrated Roof 1 Sukamukti) - Suharyanto Soro; Nana Herdiana Abdul Rahman; Didi Sunardiana; Ubun Ubun (Global Education Journal, 2026)
The background of this research is that there is a gap between the demands of the ideal curriculum emphasizing the development of in-depth teaching materials and the reality of copy-paste habits and administrative burdens that hinder teachers' creativity. This study aims to analyze the implementation of the preparation of teaching modules in the Independent Curriculum in improving teachers' professional competence. The research method used is qualitative descriptive with a case study approach. Data collection was carried out through non-participatory observation methods, in-depth interviews, and document studies, which were then analyzed through the stages of condensation, data presentation, and conclusion drawn. The results of the study show that (1) The process of preparing the Teaching Module independently functions as an effective forcing mechanism for self-upgrading teachers; (2) The activity of studying learning outcomes and compiling teaching materials requires teachers to re-validate their scientific concepts, thereby strengthening the structure of thinking and mastery of the material (professional competence). The conclusion of this study is that the implementation of the preparation of teaching modules in the independent curriculum can improve teachers' professional competence if carried out through a collaborative learning community.